РОЗВИТОК СИСТЕМИ МОТИВАЦІЙНОГО МЕНЕДЖМЕНТУ НА ПІДПРИЄМСТВАХ ІТ-СФЕРИ В УМОВАХ ЦИФРОВОЇ ТРАНСФОРМАЦІЇ - Chernov, Andrii (Zhytomyr Ivan Franko State University, 2025)
The article considers theoretical and practical aspects of the development of the motivational management system at IT enterprises in the context of digital transformation. The influence of motivation on the activation of the activities of IT employees is determined. It is proven that the modern IT industry is characterized by high global competition, dynamism and the need for constant improvement of human capital, which determines the need to create effective motivational mechanisms for personnel management. The essence of the concept of "motivational management" as a system of managerial influences aimed at forming internal and external incentives for the effective work of employees is analyzed. Particular attention is paid to the transformation of motivational approaches under the influence of the digitalization of business processes, the introduction of flexible employment models, remote work and productivity management tools through digital platforms. The role of intangible motivation, which is of particular importance in IT companies, where the key factors of employee satisfaction are professional development opportunities, autonomy in decision-making, involvement in innovative projects, corporate culture and a favorable psychological climate, is studied. It is revealed that effective motivational management should be based on a combination of material incentives with a system of socio-psychological and organizational factors that form trust, loyalty and team interaction. The study analyzes current trends in the field of personnel motivation management in IT companies. It is substantiated that digital transformation creates new opportunities for the formation of intelligent motivation management systems based on data analysis, automation of HR processes and the introduction of artificial intelligence into management decisions. At the same time, risks associated with the loss of personal contact, a decrease in emotional involvement and professional burnout of employees in virtual teams are identified. The article proposes a model for the development of a motivational management system for an IT enterprise, combining digital tools, innovative incentive methods and a value-based approach to personnel management. The results of the study are of practical importance for IT company managers, HR managers and scientists dealing with the problems of personnel management in the digital age. The implementation of the proposed approaches will contribute to increasing the efficiency of organizational activities, strengthening competitive advantages and forming a high level of involvement and professional motivation of employees in the field of information technologies.